2018
DOI: 10.2147/cmar.s167432
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated expression of miR-421 is associated with poor prognosis in non-small-cell lung cancer

Abstract: BackgroundNon-small-cell lung cancer (NSCLC) represents the most frequent subtype of lung cancer. MicroRNAs (miRNAs) have attracted a lot of attention with regard to their clinical significance and crucial biological functions in various human cancers. This study aimed to investigate the prognostic significance of microRNA-421 (miR-421) and its correlation with tumor progression in NSCLC.Materials and methodsExpression levels of miR-421 in both serum and tissue samples were measured by quantitative real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Four different analytical programs were used to reveal that miR-421 could target ORP8. Previous research has revealed that miR-421 expression is upregulated and associated with poor prognosis in non-small-cell lung cancer (29). The present experiments revealed the role of miR-421 by determining that it targets ORP8, indicating that the upregulated miR-421 expression led to the reduction of ORP8 expression in NSCLC cells.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Four different analytical programs were used to reveal that miR-421 could target ORP8. Previous research has revealed that miR-421 expression is upregulated and associated with poor prognosis in non-small-cell lung cancer (29). The present experiments revealed the role of miR-421 by determining that it targets ORP8, indicating that the upregulated miR-421 expression led to the reduction of ORP8 expression in NSCLC cells.…”
Section: Discussionsupporting
confidence: 53%
“…ORP8 is a target of miR-421. Studies have revealed that upregulated miR-421 expression is associated with poor prognosis in NSCLC (29). Therefore, it was assessed whether the downregulation of ORP8 in NSCLC was due to miR-421 dysregulation.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of miR-193b in glioma patients serves as a candidate diagnostic and prognostic biomarker [28]. In NSCLC patients, there are also some miRNAs members that have been determined as potential prognostic indicators, such as miR-126 [29], miR-451 [30] and miR-421 [31]. According to the survival analysis, this study obtained evidence for miR-1298 as an independent prognostic biomarker in the patients with NSCLC, which indicated by the survival curves and Cox regression analysis data.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs with deregulated expression values play important roles in tumorigenesis. For example, increased expression of miR-421 was observed in non-small-cell lung cancer patients and demonstrated to serve as a prognostic biomarker and tumor progression regulator [18]. Downregulated expression of miR-383-5p was detected in gastric cancer patients, which was related with a shorter survival time, tumor size, and differentiation grades and determined as a tumor suppressor [19].…”
Section: Discussionmentioning
confidence: 99%